Influence of growth stage on the chemical composition, antimicrobial, and antioxidant potential of Cymbopogon martinii (Roxb.) Wats. essential oil - Sonigra, Priyankaraj; Meena, Mukesh (Frontiers in Plant Science, 2025)
IntroductionCymbopogon martinii (Roxb.) Wats. essential oil (CMEO) exhibits significant variation in composition and bioactivity across different growth stages. Understanding these changes is crucial for optimizing its therapeutic and industrial applications.MethodsCMEO was extracted at the vegetative, reproductive, and post-reproductive stages using hydro-distillation. Chemical composition was analyzed by GC-MS. Antimicrobial activity was assessed using disc diffusion and direct contact assays, while antioxidant potential was evaluated through DPPH, ABTS, and β-carotene bleaching assays. Correlation analysis was performed to link major bioactive compounds with biological activities.ResultsA total of 59 compounds were identified, with the reproductive stage showing the highest diversity (49 compounds, 97.86%) and oil yield. Major compounds varied across stages: carveol (20.87%), trans-p-mentha-1(7),8-dien-2-ol (12.9%), and D-limonene (6.2%) dominated the vegetative phase; cis-piperitol (15.27%), cis-p-mentha-1(7),8-dien-2-ol (15.52%), and carvone (3.31%) were abundant in the reproductive phase; while the post-reproductive phase was rich in trans-p-mentha-1(7),8-dien-2-ol (19.58%) and carveol (11.32%). Antibacterial and antifungal activities were highest during the reproductive stage, particularly against Staphylococcus aureus and Alternaria alstroemeriae. Antioxidant potential peaked during the post-reproductive phase, with the lowest IC50 values.DiscussionCorrelation analysis revealed negative associations between key bioactive compounds (e.g., carvone, D-limonene, α-methylcinnamaldehyde, and (S)-perillyl alcohol) and microbial/oxidative inhibition thresholds, confirming their contribution to CMEO bioactivity. These findings highlight the critical role of harvest timing in maximizing the chemical richness, antimicrobial efficacy, and antioxidant potential of CMEO.